Time-Dependent Variations in Structure of Sheep Wool Irradiated by Electron Beam - Zuzana Hanzlíková; Michael Kenneth Lawson; Peter Hybler; Marko Fülöp; Mária Porubská (Advances in Materials Science and Engineering)
Wool scoured in tap water with no special degreasing and containing a balanced humidity responding to usual laboratory conditions was irradiated by accelerated electron beam in the range of 0–350 kGy dose. Time variations of the wool structure were measured using FTIR, Raman, and EPR spectroscopy. The aim was to determine whether preexposure treatment of the wool, as well as postexposure time, affects the properties of the irradiated wool. Reactive products such as S-sulfonate, cystine monoxide, cystine dioxide, cysteic acid, disulphides, and carboxylates displayed a considerable fluctuation in quantity depending on both the absorbed dose and time. Mutual transformations of S-oxidized products into cysteic acid appeared to be faster than those in dry and degreased wool assuming that the present humidity inside the fibres is decisive as an oxygen source. EPR results indicated a longer lifetime for free radicals induced by lower doses compared with the radicals generated by higher ones. The pattern of the conformational composition of the secondary structure (α-helix, β-sheet, random, and residual conformations) also showed a large variability depending on absorbed dose as well as postexposure time. The most stable secondary structure was observed in nonirradiated wool but even this showed a small but observable change after a longer time, too.